EXPLORING THE USAGE OF THE INTERNET AMONG MASS MEDIA COMMUNICATION STUDENTS - P., Tamil Selvan; Kalaiyarasan, G.; Kumar, K. Sathish; Ramnath, R.; Govindarajan, K.; Jayanthy, A. Catherin; Sasikumar, N.; Mahendraprabu, M. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study investigated the usage of the Internet among mass media communication students. Additionally, fine arts students are compared according to the sub-variable Gender, Parents’ Educational status, and Digital devices. The researcher employed survey method and collected the data in person. Four-point scale questionnaires were used to collect data in this research. In such a context, the data was collected among 152 mass media communication students who were studying in second level degree. Finally, this study has found that do not show any significant difference in usage of Internet between the demographic variables gender, parents’ educational status such as male and female, school education and higher education. Though, has been found that there is a significant difference in usage of Internet among the demographic variable of digital devices use mostly such as cell phone, laptop, desktop, cell phone with others.